Risk of maternal mortality in women with severe anaemia during pregnancy and post partum: a multilevel analysis - Jahnavi Daru, MBBS; Javier Zamora, ProfPhD; Borja M Fernández-Félix, MSc; Joshua Vogel, PhD; Olufemi T Oladapo, FWACS; Naho Morisaki, PhD; Özge Tunçalp, PhD; Maria Regina Torloni, PhD; Suneeta Mittal, MD; Kapila Jayaratne, MD; Pisake Lumbiganon, ProfMD; Ganchimeg Togoobaatar, PhD; et al. (Elsevier, 2018)
Summary: Background: Anaemia affects as many as half of all pregnant women in low-income and middle-income countries, but the burden of disease and associated maternal mortality are not robustly quantified. We aimed to assess the association between severe anaemia and maternal death with data from the WHO Multicountry Survey on maternal and newborn health. Methods: We used multilevel and propensity score regression analyses to establish the relation between severe anaemia and maternal death in 359 health facilities in 29 countries across Latin America, Africa, the Western Pacific, eastern Mediterranean, and southeast Asia. Severe anaemia was defined as antenatal or postnatal haemoglobin concentrations of less than 70 g/L in a blood sample obtained before death. Maternal death was defined as death any time after admission until the seventh day post partum or discharge. In regression analyses, we adjusted for post-partum haemorrhage, general anaesthesia, admission to intensive care, sepsis, pre-eclampsia or eclampsia, thrombocytopenia, shock, massive transfusion, severe oliguria, failure to form clots, and severe acidosis as confounding variables. These variables were used to develop the propensity score. Findings: 312 281 women admitted in labour or with ectopic pregnancies were included in the adjusted multilevel logistic analysis, and 12 470 were included in the propensity score regression analysis. The adjusted odds ratio for maternal death in women with severe anaemia compared with those without severe anaemia was 2·36 (95% CI 1·60-3·48). In the propensity score analysis, severe anaemia was also associated with maternal death (adjusted odds ratio 1·86 [95% CI 1·39-2·49]). Interpretation: Prevention and treatment of anaemia during pregnancy and post partum should remain a global public health and research priority. Funding: Barts and the London Charity.